Efficacy of Bacille Calmette–Guérin Against COVID-19 Hospitalisation: A Meta-Analysis and Systematic Review of Randomised Control Trials - Joseph Inauen; Sam LaBroome; Antonietta Maldari; Natalie E. Stevens; James B. Geake; David J. Lynn; Simone Barry (Vaccines)
Background: The BCG vaccine has long been hypothesised to have non-specific protective effects, and early epidemiological studies on COVID-19 suggested a possible protective effect against SARS-CoV-2 infection and COVID-19 severity. This systematic review and meta-analysis assesses the effect of the BCG vaccine on preventing severe COVID-19 disease, based on the rate of hospitalisation for COVID-19 related disease. Methods: We performed a literature search of randomised control trials comparing BCG vaccine to placebo in adult participants using EMBASE, MEDLINE, and Web of Science. A random effects model was used to generate summary estimates. Risk of bias was assessed regarding randomisation, allocation sequence concealment, blinding, incomplete outcome data, selective outcome reporting, and other biases. Results: We included 11 studies involving 18,412 participants, reporting COVID-19 incidence. The hospitalisation rate was sought from the authors of papers that did not report on this statistic. There was no significant reduction in COVID-19-related hospitalisation across all studies (relative risk 0.85, 0.51–1.40, p = 0.335), COVID-19 incidence across all studies (relative risk 1.07, 0.94–1.21, p = 0.264), deaths reported in six studies (relative risk 0.67, 0.36–1.26, p = 0.733), and COVID-19-related critical care admissions reported in four studies (relative risk 0.43, 0.13–1.46, p = 0.746). Conclusions: The findings from this meta-analysis, involving a large number of participants, suggest no protective effect of BCG vaccination against severe COVID-19 outcomes or overall SARS-CoV-2 incidence. Further research may be needed to explore the potential non-specific effects of BCG vaccination in other specific populations and against other infections.